Correlates of business survival: Empirical evidence on youth-owned micro and small enterprises in Urban Ethiopia - Tasssew Woldehanna; Wolday Amha; Manex B. Yonis (IZA Journal of Development and Migration, 2018)
This paper investigates the effects of person-, firm-, industry-, and business strategy-specific characteristics on the survival of youth-owned urban micro and small enterprises in Ethiopia. It employs nonparametric and semi-parametric methodologies using a retrospective data. The hazard rate reaches the highest point at business 2 years for micro enterprises and 4 years for small enterprises. Owner-, firm-, and industry-specific characteristics are important factors for micro and small enterprises' (MSEs') survival. Marketing and financial management strategies are playing a crucial role on extending MSEs' survival duration. The study implies there should be more effective and longer period of support for micro than small enterprises.
Keywords: C14; C41; D21; J23; L26; M21; 330; Youth self-employment; Micro- and small-scale enterprises; Hazard model